2017
DOI: 10.1016/j.explore.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Osteopathic Manual Therapy and Rehabilitation for Subacromial Impingement Syndrome: A Case Report

Abstract: Rotator cuff dysfunction is common in athletes involved with overhead sports. Secondary subacromial impingement is a common cause of pain for patients with rotator cuff dysfunction. Exercise rehabilitation and manual therapy can be used in the treatment of subacromial impingement to decrease pain, increase functionality and support a return to activity. The current case report describes a 24-year-old patient with supraspinatus tendinosis and secondary subacromial impingement who was experiencing pain when play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several case studies have also reported osteopaths prescribing exercise as a form of therapy or where it has been incorporated into the patients' broader management plan [ 30 32 ]. The use of exercise outside the immediate osteopathy practice environment has also been investigated with home exercise programmes featured in various manual therapy research studies [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies have also reported osteopaths prescribing exercise as a form of therapy or where it has been incorporated into the patients' broader management plan [ 30 32 ]. The use of exercise outside the immediate osteopathy practice environment has also been investigated with home exercise programmes featured in various manual therapy research studies [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that manual therapy (MT) treatment over a 6-week period is effective to reduce pain and improve function in patients suffering from subacromial impingement syndrome [16]. Conservative management minimizes the inflammation and discomfort and facilitates rotator cuff tissue repair [17].…”
Section: Introductionmentioning
confidence: 99%